Nutritional and Health Status of Autistic Children: Assessing the Efficacy of Gluten-Free High-Protein Bread in Improving Biochemical Parameters - Saleh Alhajri, Ahlam; Alkubaisi, Abdullah; Saad Aljamaan, Nahla; Mohammed Alamer, Maitham (Journal of Neonatal Surgery, 2025)
Background: The issue of the nutritional and health status of children with autism spectrum disorders (ASD) is intricate and encompasses dietary factors. High gluten foods consumption is a significant concern due to its potential influence on health and autism symptoms. Investigating this connection can offer valuable information for enhancing the well-being of autistic children. Methods: This study investigated the effects of gluten-free, high-protein meals on autistic children by examining changes in biochemical markers pre and post a three-month regimen of thrice-daily consumption of chickpea and okra-based bread. The study involved 100 boys with ASD between the ages of 9 and 11. Their physical measurements, health problems, socioeconomic background, dietary habits, and metabolic index were examined. Results: The study found common health issues in ASD children, including lethargy, solitary eating habits, decreased appetite, and bloating. In terms of body weight, 51% were within a normal range, while 48% were overweight/obese. Significant discrepancies were observed in their consumption of energy, carbohydrates, and fats when compared to standard dietary guidelines. After the dietary change, there was a marked improvement in the levels of essential minerals and vitamins. Enhanced levels of GSH, GSSG, and CoQ10, alongside reduced NADPH, NADH, and ATP levels were noted, which were likely due to increased protein and fiber in the gluten-free bread. Conclusions: The introduction of a gluten-free and high-protein bread using chickpeas and okara demonstrated positive outcomes, enhancing essential mineral and vitamin levels. Additionally, observed biochemical changes suggest potential benefits of this dietary intervention in addressing metabolic imbalances commonly associated with ASD.